CASE STUDY: MEMORANDUM AND CAUSES OF EVASION OF STUDENTS IFAL-CAMPUS MARAGOGI (Fiep Bulletin - online, 2014)
On August 23, 2010, the first selection process, through public lottery, with a total of 562 subscribers was conducted, with 190 candidates competed for the 80 slots of the Integrated Technical Course in Agroecology and 372 candidates competed for the 80 vacancies Course Integrated technician lodging. The Institute aims to ensure the right of all to a quality education, developing skills, attitudes, autonomy, independence and creativity of individuals. Based on this assumption, we glimpse a guiding principle integrating Vocational Education - Work - Local Development. This project is justified by the need and lack of studies on truancy, in order to intervene in the teaching-learning process by seeking to reduce the dropout rate of students from the Federal Institute of Alagoas/Campus Maragogi. Apply to students graduating with a questionnaire as a diagnostic to identify the causes and reasons for dropout students Campus Maragogi review. It is expected that the results will serve as input for new research, taking into consideration that the theme will fill a void and an emptiness of the reasons and causes of dropout students IFAL/Campus Maragogi, generating what is unknown and a randomly change of educational paradigm and then intervene in the school context reflecting methodological changes and new teaching strategies.
Keywords: Case Study; Reasons and Causes; School Failure Hip.